Washathiyyah Character of Muslim Generation in the Perspective of Abdullah Nashih Ulwan, Hamka and Zakiah Drajat - Acela, Nuriza; Adlani, Nazri (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
This study discusses character education in instilling washathiyyah values for the Muslim generation. Some Indonesian scholars who study the value of washathiyyah are Abdullah Nashih Ulwan, Hamka, and Zakiah Drajat. They are a row of scholars who spend all their lives inviting people to goodness through their works, pens and oral advice. Through their works and thoughts, they have contributed a lot in accompanying the journey of Muslims, especially in practicing the religion that is Rahmatan Lil 'Alamin. This research is a descriptive literature review with qualitative research. From the results of the study, it can be concluded that Abdullah Nashih Ulwan stipulates that the cultivation of washathiyyah Islamic values in building character must be carried out at every marhalah of the human journey from the age of conception, the phase of children, adolescents, and adults. likewise, the type of parenting will affect the growth and development of children as a generation of Muslims. There are parenting patterns that are democratic, authoritarian, permissive, and neglectful. Hamka views that the applied parenting should contain the values of shaja'ah, iffah, wisdom, and adl. Zakiah Drajat reveals feelings, behavior /actions, healthy body and mind as the key to grounding washathiyyah values for the Muslim generation. It is hoped that this paper will be able to provide an overview of the Indonesian Muslim Ulama and a reference for writing scientific papers based on the views of the three Ulama.